Effect and mechanisms of reproductive tract infection on oxidative stress parameters, sperm DNA fragmentation, and semen quality in infertile males - Kang-Sheng Liu; Xiao-Dong Mao; Feng Pan; Rui Fang An (BMC, 2021)
Abstract Recent years have seen a rising incidence of male infertility, mostly caused by the decline of sperm quality. The ratio of infertile males to infertile females has escalated from 3:7 in 2013 to current 5:5, which turns male infertility into the research focus of reproductive medicine. This study aimed to clarify the effect of reproductive tract infection by ureaplasma urealyticum (UU) and chlamydia trachomatis (CT) on the DNA integrity and routine semen parameters of infertile males. A retrospective study was performed. A total of 259 infertile males who were treated at the Andrological Laboratory Examination and Reproductive Medicine Center in our hospital were analyzed. qRT-PCR was used to examine the infection status of CT and UU. According to the eligibility criteria, we evaluated the semen parameters and biochemical data of 253 men. Based on the results of PCR, the subjects were divided into four groups: Group I (CT positive, 63 cases), Group II (UU positive, 60 cases), Group III (CT positive and UU positive, 62 cases), and Group IV (no infection, 68 cases). DNA fragmentation index (DFI), sperm count, vitality and morphology, elastase level, seminal plasma malondialdehyde (MDA), and total antioxidant capacity (TAC) were assessed. Compared to Group IV, three groups (Group I, Group II and Group III) showed difference in semen volume, proportion of sperm with normal morphology, sperm motility, progressive motility, and vitality (P < 0.05). Compared to Group IV, Group II and Group III showed difference in DFI (P < 0.05). Compared to Group IV, Group II and Group III showed difference in elastase level (P < 0.05). VCL, VSL, VAP, WOB, ROS, TM, HDS showed differences between groups of abnormal/normal WBC (*P < 0.01). UU infection significantly increased the level of seminal leukocytes only in Group II, but not in the other three groups, indicating that UU is a factor to increase the level of seminal leukocytes. Compared with the normal leukocyte group, there were significant differences in total motility, forward motility and normal sperm ratio between the two groups. The proportion of sperm with abnormal morphology (mostly in the head) showed obvious difference between groups of high and normal seminal leukocytic levels. At the same time, in this study, SCGE and SCD verified that leukocytes could damage sperm DNA by increasing ROS, which ultimately affects male fertility.